Analysis of Islamic Messages in the Lyrics of Sawéran Local Wisdom in The Pasirtamiang Communities in Ciamis - Nani Widiawati; Ela Nurlaela Fitriyani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
The research is focused on finding the social, geographical, and religious context of the sawéran tradition in the Muslim community of Pasirtamiang, the dynamics of the message narrative in the sawéran lyrics, and the Islamic values and messages contained therein. This focus is important so that the dialectic between religion and culture, which is sometimes seen as a form of syncretism that endangers religion's existence, can be clarified. In this writing, the Muslim community of Pasirtamiang shows a fairly representative model of religious and cultural dialectics so that their people can preserve their cultural heritage without losing their Islamic identity. The research used explanative methods to find causal relationships between local wisdom facts identified by participant observation and in-depth interviews. The results showed that the socio-geographic and religious factors of the Pasirtamiang community also influenced the development process of the sawéran tradition. The format and substance of the sawéran content have transformed, the lyrics are simpler, and the Islamic values are emphasized, both technically and substantially. Islamic values in the lyrics sawéran are classified into divine, spiritual, and moral values. Overall, the content of sawéran's lyrics is an integral part of the Islamic message.Penelitian difokuskan untuk menemukan konteks sosial, geografis, dan religius tradisi sawéran dalam masyarakat muslim Pasirtamiang, dinamika narasi pesan dalam lirik saweran, serta nilai dan pesan Islam yang terkandung di dalamnya. Fokus ini penting supaya dialektika antara agama dan budaya, yang terkadang ditengarai sebagai bentuk sinkretisme yang membahayakan eksistensi agama, dapat diklarifikasi. Dalam tulisan ini, masyarakat muslim Pasirtamiang menunjukkan model dialektika agama dan budaya yang cukup representatif sehingga masyarakatnya dapat melestarikan warisan budaya tanpa kehilangan identitas keislamannya. Penelitian ini menggunakan metode eksplanatif untuk menemukan hubungan kausalitas antara fakta kearifan lokal yang diidentifikasi melalui observasi partisipan dan wawancara mendalam. Hasil penelitian menunjukkan bahwa faktor sosial-geografis dan keagamaan masyarakat Pasirtamiang turut mempengaruhi proses perkembangan tradisi sawéran. Format dan substansi isi sawéran telah mengalami transformasi, penuturan liriknya lebih sederhana dan semakin menegaskan nilai-nilai keislaman, baik secara teknis maupun substansial. Nilai-nilai Islam dalam lirik sawéran diklasifikasikan menjadi nilai ketuhanan, spiritual, dan moral. Secara keseluruhan, isi lirik sawéran merupakan bagian tak terpisahkan dari pesan Islam.